Spontaneous Achilles Tendon Rupture During Farm Work Repaired by Partially Threaded Malleolar Screw and Plantaris Autograft in a Limited-Resource Hospital: A Rare Case Report - Andri Danika; Andi Muhammad Ihsan Fauzan; Aan Tri Lutfi Muhammad; Hisyam Hartaman Putra; Naravitto Ad-Dimasyqi; Agung Bipayana Adi Wibowo; Muhammad Farhan Fathurrahman; Agus Saribudaya (International Medical Journal Corp. Ltd, 2026)
Introduction: Achilles tendon rupture is a common musculoskeletal injury, most frequently affecting athletes and typically occurring at the mid-substance of the tendon. Insertional avulsion rupture is rare, particularly in non-athletic populations, and its management may be challenging in limited-resource settings. Case Presentation: A 55-year-old male farmer presented with sudden onset of severe left ankle pain following forced dorsiflexion while working in a rice field. Clinical examination revealed a positive Thompson test. Intraoperative findings confirmed an insertional avulsion rupture of the Achilles tendon with degenerative changes. Due to limited availability of standard fixation devices, surgical repair was performed using a partially threaded malleolar screw with washer for tendon-to-bone fixation, augmented with an autologous plantaris tendon graft. At three months of follow-up, the patient was able to ambulate with minimal assistance, reported no pain, and demonstrated restoration of tendon continuity with a negative Thompson test. Conclusion: This case illustrates a rare presentation of insertional Achilles tendon rupture in a non-athletic occupational setting. The use of a partially threaded malleolar screw combined with plantaris tendon autograft may represent a practical and effective alternative for Achilles tendon reconstruction in healthcare facilities with limited resources.